Relación entre el gasto público social y la pobreza en Ecuador usando datos de series de tiempo durante el periodo de 1990 al 2022. - Uchuari Vera, María José (2024)
The comprehensive development of individuals is limited by the lack of economic resources, which obstructs access to needs such as food, housing, education and essential services for their full development. Poverty is embedded due to inequality and absence of opportunities, which affects collective well-being by hindering economic growth and weakening social cohesion. In response to this, governments implement investment policies in social projects in order to reduce poverty. The objective of this research is to evaluate the effect of social public spending on poverty in Ecuador during the period of 1990-2022, through a statistical and econometric analysis, proposing policies to reduce poverty levels in the country. For its development, the relationship between poverty, social public spending, corruption, unemployment and economic growth is analyzed through VAR and VEC time series models, applying Granger and Breitung- Candelon causality tests. The data was obtained from the World Bank, World Health Organization and Varieties of Democracy. The main result suggests that a 1% increase in public social spending reduces poverty by 3.81%. In addition, there is a short- and long-term relationship, and a causal relationship between these variables. Based on the findings, it is suggested that social investment programs and projects be supported in areas such as education, health, and basic infrastructure for the most disadvantaged groups, both in rural and urban areas, which improve the quality of life and establish principles for long-term sustainable development. In addition, it is recommended that institutions be strengthened through comprehensive, monitored policies, diversify the economy, and generate employment.